Introduction of Financial Literacy In Children To Form Superior Character In Money Management - Hasanah, Wardah Amrillah; Hilda Dwiyanti; Anggraeni, Reinita; Gunawan, Ade; Sholihah, Ria Anisatus; Adinugraha, Hendri Hermawan (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
Financial literacy from an early age for children is crucial for them when they grow up and enter a productive period in the future. Through community service programs, children are given an in-depth understanding of financial literacy, money management, and saving. Field survey results show that children's financial literacy levels are still low; most children use pocket money for consumptive expenses such as food and toys with little savings. This community service activity aims to provide knowledge and understanding about financial literacy through savings activities. The main goal is for children to become more familiar with money, manage money wisely, and realize the importance of saving for their future. The method applied in this activity is socialization, which involves lectures, savings practice simulations, and question-and-answer sessions. Children are taught how to manage money wisely and understand the concept of financial literacy. The activity results show an increase in children's understanding of how to use money wisely, as well as fostering a desire to save. The hope is that this program will continue to provide sustainable benefits for children in understanding and managing finances in the future.